Culture as politics selected writings of Christopher Caudwell - Caudwell, Christopher 1907-1937; Margolies, David (New York Monthly Review Press, 2018)
"Selected essays by Christopher Caudwell, on culture, psychology, and capitalism. Material drawn from Caudwell's previous book, "Illusion and Reality, Studies in a Dying Culture" and his essay, "Heredity and Development.""--Provided by publisher.
D. H. Lawrence : a study of the bourgeois artist -- Freud : a study in bourgeois psychology -- Liberty : a study in bourgeois illusion -- The birth of poetry -- The death of mythology -- The development of modern poetry -- English poets I : the period of primitive accumulation -- English poets II : the industrial revolution -- English poets III : the decline of capitalism -- The movement of bourgeois poetry -- The world and the "I" -- Heredity and development : a study of bourgeois biology.
Includes bibliographical references and index.
Keywords: Civilization, Modern -- 20th century; Marxist criticism